Study of Epidemiological Factors Affecting Patients of Hypertension Attending Urban Health Training Centre of Community Medicine of Tertiary Care Hospital, Maharashtra (Indian Journal of Public Health Research & Development, 2020)
Introduction -Hypertension is a chronic condition causing coronary heart disease, stroke and other vascularcomplications. Aim and objective- To study epidemiological factors affecting patients of hypertensionattending urban health training centre of community medicine department of tertiary care hospital,Maharashtra. Material and Methods- The study was a hospital based observational descriptive studycarried out in urban health training centre of community medicine department of tertiary care hospital fromApril 2016 to September 2016 including all known cases of hypertension which was around 450. Result-Maximum cases were from age group 40-59 years (53.71 %) and 40.77 % were males and 59.23 % werefemales.Whereas 43 % and 14 % of study subjects were having BMI of 25-29.9 and ? 30 respectively, 35% were having family history of hypertension, 72% were having salt intake of > 5 gram, 67% were havingmixed diet, 55 % men were having waist-hip ratio > 0.9 and 67% women were having waist-hip ratio >0.8,45 % of total male subjects and 08 % female subjects were having habit of alcohol intake. Whereas 42 %of total male subjects and 28 % of female subjects were having habit of tobacco intake. Conclusion- Forthe control of hypertension decreased salt intake, physical activity, cessation of habits such as alcohol andtobacco intake and early detection and treatment are need of the hour.
Keywords: Epidemiological factors, Hypertension, Tertiary care hospital